If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = p + 1 Reorder the terms: 19 = 1 + p Solving 19 = 1 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 19 + -1p = 1 + p + -1p Combine like terms: p + -1p = 0 19 + -1p = 1 + 0 19 + -1p = 1 Add '-19' to each side of the equation. 19 + -19 + -1p = 1 + -19 Combine like terms: 19 + -19 = 0 0 + -1p = 1 + -19 -1p = 1 + -19 Combine like terms: 1 + -19 = -18 -1p = -18 Divide each side by '-1'. p = 18 Simplifying p = 18
| -6+3x+8=-210 | | 8a-(-3a)= | | 2x^4+3x^3-2x^2+14x+15=0 | | 4x-8=1+7x | | q-4=69 | | -3(5+5x)=-105 | | 3d=78 | | 1/3(6y-9)=2y=13 | | -14=q3 | | 3.14*35=109.9 | | 3d=73 | | rs+4= | | 50=h+-43 | | 10x-(8/3)-4x=6x | | h=-16t^2+55t+5 | | 3x-3(2x+4)=10 | | 3.14*35= | | h/2=1.63 | | 3(10-4)/(15-3*3) | | -12+20(x)=588 | | 96/0.40 | | 5n^2=1+5n | | f-3=2 | | k/4=3 | | 4x^2+12w+9=49 | | 18x^2-66x-252=0 | | u-4=15 | | a*3+4=10 | | y^2+10y+25-x^2=0 | | -6-7=6x+10-5x | | -32+5(12)= | | 1-n-2n=1-2n-n |